2013
DOI: 10.1002/14651858.cd002878.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal non-invasive positive pressure ventilation for stable chronic obstructive pulmonary disease

Abstract: Background Non-invasive positive pressure ventilation (NIPPV) is effective in treating acute exacerbations of chronic obstructive pulmonary disease (COPD). Nocturnal non-invasive positive pressure ventilation (nocturnal-NIPPV) has been proposed as an intervention for stable hypercapnic patients with COPD. Objectives To assess the effects of nocturnal-NIPPV at home via nasal mask or face mask in people with COPD by using a meta-analysis based on individual patient data (IPD). Search methods We searched the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 27 publications
0
66
0
5
Order By: Relevance
“…A recent Cochrane review 110,124 has incorporated IPD analyses but based on a smaller group of studies and without considering hospitalisations or survival. The Cochrane analysis was not aimed at identifying potential effect modifiers.…”
Section: Overarching Discussion and Future Research Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent Cochrane review 110,124 has incorporated IPD analyses but based on a smaller group of studies and without considering hospitalisations or survival. The Cochrane analysis was not aimed at identifying potential effect modifiers.…”
Section: Overarching Discussion and Future Research Recommendationsmentioning
confidence: 99%
“…110,[114][115][116][117][118][119][120] 114 The recent guidelines 120 are also not considered further, as their findings are based on systematic reviews discussed here. However, all the reviews had reasonably similar aims to the current review with, in most cases, a focus more on the physiological outcomes and less on those outcomes that might more readily populate an economic model to determine cost-effectiveness from a health-service provision perspective.…”
Section: Review Of Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…This metaanalysis showed that 3 months of NIPPV in patients with stable COPD did not improve lung function, gas exchange, sleep efficiency, or 6-minute walking distance. [11,12] Casanova and colleagues studied the effects of longterm NIPPV (a duration of 12 months) to either NIPPV plus standard care or to standard care alone. The number of hospital admissions was lower after 3 months (5% vs 15%).…”
Section: Uncontrolled Trialsmentioning
confidence: 99%
“…Restrictive thoracic disorders (RTD) (including thoracic cage deformities and neuromuscular disorders (NMD)), obesity hypoventilation syndrome (OHS) and stable chronic obstructive pulmonary disease (COPD) with severe hypercapnia and nocturnal desaturation can be listed as the appropriate indications for domiciliary NIV use. NIV has been shown to decrease somnolence, fatigue and dyspnea with improved quality of life and survival in selected patients with these disorders (especially for amyotrophic lateral sclerosis (ALS), RTD, OHS) 6; whereas its role in stable COPD still remains controversial (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%